Evaluation of Silicon Bioavailability in Soil with Different Chemical Extractants - Meirelles, Guilherme Constantino [UNESP]; Deus, Angélica Cristina Fernandes [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Bull, Leonardo Theodoro [UNESP] (Springer Nature, 2022)
Aim: This study was developed to examine the extracting power and efficiency of different methods in order to identify those that best correlate the available Si in the soil with Si uptake by plants. Methods: We evaluated alterations in soil-Si extraction methods using the calcium chloride (CaCl2), acetic acid and ion-exchange resin extractants. Eighteen soils were used and modifications were made in the speed and duration of soil/extractant solution shaking and extracting solution concentration. Quantification was achieved by colorimetry and inductively coupled plasma-optical emission spectrometry (ICP-OES). The experiment was carried out in a greenhouse where rice was cultivated until 60 days after emergence. Relative cumulative frequency and the correlation between Si accumulated in the rice plant shoots and Si extracted from the soil by different methods were determined. Results: In terms of relative cumulative frequency, resin showed the least capacity to extract Si from the soil, while acetic acid exhibited the highest extracting power. The methods involving calcium chloride as the extractant showed correlation coefficients between soil extractable Si and Si accumulated in the plant above 0.90, whereas the correlation obtained in the majority of acetic acid methods and in one resin method was greater than 0.80. Conclusions: The extractants have different capacities to extract silicon from soil, and the acetic acid, calcium chloride and resin methods with 12 h of shaking showed a high correlation between soil extractable silicon and silicon accumulation in the rice plant shoots.
Keywords: Acetic acid; Calcium chloride; Oryza sativa; Resin